Muscle activation in world-champion, world-class, and national breaststroke swimmers - Olstad, B. H.; Zinner, C.; Rocha Vaz, J.; Cabri, J. M. H.; Kjendlie, P.-L. (International Journal of Sports Physiology and Performance, 2017)
Purpose: To investigate the muscle-activation patterns and coactivation with the support of kinematics in some of the world`s best breaststrokers and identify performance discriminants related to national elites at maximal effort.